Sociodemographic factors and lifestyles in obstetrics students of universidad - Castillo Ruiz, Verónica (2020)
Objective. To determine the sociodemographic factors and lifestyles of students from Professional Academic School of Obstetrics at Universidad de Huánuco, Leoncio Prado branch. Methods.A non-experimental, cross-sectional design study was carried out with a sample of 168 students. They were selected and chosen in a non-random, non-probabilistic manner. A questionnaire and a scale were  used to measure the variables under study. Chi-square test of independence was used in inferential analysis with a statistical significance of p ≤ 0.05. Results. 60.3 % (101) of the students have unhealthy lifestyles, and 39.7 % (67) presented healthy lifestyles. Statistical significance was found in the sociodemographic factors at the age of 20 to 24 years 43.7 % (73), female gender 94.6 % (159),  and single marital status 85.1 % (143). Conclusion. Sociodemographic factors are related to lifestyles in the students of Professional Academic School of Obstetrics at Universidad de Huánuco, Leoncio Prado branch.